The Importance of Money in the System of Economic Relations - V. A. Varfolomeeva; A. V. Gribanov (Путеводитель предпринимателя, 2022)
Analysis of the development of monetary theories indicates the importance of money in the system of economic relations. The article defines: the role, qualities, functions of money. The author mentions the gradual development of the digital ruble. In conclusion, the author points out that money is the embodiment of the economic power of the state and is intended to maintain it.